Pengembangan Panduan Bimbingan Kelompok dengan Teknik Fun Outbound untuk Meningkatkan Perilaku Altruis Siswa Sekolah Menengah Pertama - Ahadinasrikin, Hanifan; Indreswari, Henny; Muslihati, Muslihati (Buletin Konseling Inovatif, 2021)
This research and development seek to construct a group counseling guideline book with a fun outbound strategy to increase junior high school students' generosity. The product was designed following the research and development procedure from Borg and Gall. The analysis results of data from guidance and counseling experts, media experts, and users validity present that this guideline is applicable to be used according to its accuracy, usability, easiness, and attractiveness. During the product validation phase, altruism and product eligibility instruments were used. The obtained data included quantitative and qualitative data. The quantitative data were analyzed using the inter-rater agreement model, while the qualitative data were analyzed by concluding the subjects' rating. The complete product's validity score shows that this counseling guideline is feasible to be used by schools' counselors in the group counseling addressed to enhance junior high school students' altruism.